2021
DOI: 10.1186/s12905-021-01194-8
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of severity in diastasis recti abdominis and pelvic floor dysfunction: a retrospective cohort study

Abstract: Background Diastasis of rectus abdominis (DRA) refers to a separation of the rectus abdominis from the linea alba. This study aimed to investigate the association with the severity of DRA for developing pelvic floor dysfunction among women during the first year postpartum. Methods This is a retrospective cohort study which collected data from 229 postpartum women. DRA was defined as a separation of ≥ 20 mm at any point 4.5 cm above, at and 4.5 cm b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
2
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 28 publications
0
29
2
6
Order By: Relevance
“…Generally, DRA is caused by endocrine factors during pregnancy, such as the relaxation of cartilage and ligaments at the joint of sacroiliac joint and phalanx, too much exertion during delivery, and improper posture of the parturient. Without treatment, DRA will not be restored to its normal anatomical position, which can lead to abdominal discomfort and low back pain in the parturient, which will seriously affect women's quality of life [6][7][8]. erefore, it is very important to diagnose DRAin time and take early measures to treat it.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, DRA is caused by endocrine factors during pregnancy, such as the relaxation of cartilage and ligaments at the joint of sacroiliac joint and phalanx, too much exertion during delivery, and improper posture of the parturient. Without treatment, DRA will not be restored to its normal anatomical position, which can lead to abdominal discomfort and low back pain in the parturient, which will seriously affect women's quality of life [6][7][8]. erefore, it is very important to diagnose DRAin time and take early measures to treat it.…”
Section: Introductionmentioning
confidence: 99%
“…[16] Análise dos desfechos Os resultados obtidos em relação aos métodos de avaliação, grupos de intervenção, frequência, intensidade e duração do programa de reabilitação e as principais conclusões estão dispostos na Tabela III. [20,22,24]. Relatos de que a incidência de diástase foi significativamente maior em mulheres que se submeteram à cesária foram encontrados em quatro estudos [20,22,24,25].…”
Section: Resultsunclassified
“…Relatos de que a incidência de diástase foi significativamente maior em mulheres que se submeteram à cesária foram encontrados em quatro estudos [20,22,24,25]. Além disso, o estudo de Fei et al [20] Apesar de a maioria dos estudos não correlacionarem a dor lombopélvica com DRA [33], os músculos abdominais estão em continuidade com a fáscia toracolombar e AP, e trabalham sinérgica e simultaneamente e, por isso, a dor lombar também pode ser atribuída a fraqueza da MAP [23]. A DRA trata-se de uma disfunção do tecido conjuntivo, e não está relacionada apenas a fatores perinatais, como muitas vezes é assumido [23].…”
Section: Resultsunclassified
See 1 more Smart Citation
“…They found that the prevalence of DRA decreased from 100% at gestational week 35 to 39% at 6 months postpartum [ 4 ]. In a recent study, Fei et al reported 82.6% as the prevalence rate in their retrospective study conducted among women in their first year of postpartum [ 5 ].…”
Section: Introductionmentioning
confidence: 99%